Economic value of agro-meteorological services: a review of the international literature - Manzvera, Joseph; Anaman, Kwabena Asomanin (Frontiers in Climate, 2026)
IntroductionThe increasing frequency and intensity of climate-induced extreme weather events, such as droughts, have significantly reduced agricultural productivity worldwide. Enhancing access to agro-meteorological services can mitigate these impacts by improving farmers’ decision-making and adaptive capacity. However, their economic value remains poorly understood, especially in African countries where meteorological services are provided as public goods. Demonstrating their value is critical to stimulate investment and strengthen climate-resilient agriculture.MethodsThis study reviews and synthesises empirical evidence on the economic value of agro-meteorological services through a systematic literature review and meta-analysis of international studies. Both peer-reviewed and grey literature were analysed to assess valuation methods, estimated benefits, and knowledge gaps.ResultsThe meta-analysis results indicate that agro-meteorological services generate an estimated annual economic value of US$0.59 billion annually, underscoring their vital role in enhancing agricultural productivity, risk management, and resilience to climate shocks. Access to reliable weather and climate information enables farmers to make informed decisions, optimise resource use, and reduce crop losses, thereby contributing to more sustainable and profitable agricultural systems.DiscussionDespite their clear economic value, political, institutional, and socio-economic factors influencing investment decisions remain underexplored. The integration of political economy analysis is essential to understand how governance structures, marginalisation, and social inequalities shape access to and benefits from agro-meteorological services.RecommendationsGovernments and development partners should increase investment in advanced meteorological infrastructure, data and communication systems, treating these services as productive investments rather than costs. Researchers should integrate indigenous weather knowledge with modern forecasting to enhance trust and usability. The economic analyses should incorporate secondary benefits across sectors using tools such as input–output analysis and general equilibrium models to better capture the full societal value of agro-meteorological services. There is also a need to incorporate political economy perspectives in future studies to better capture how social and structural inequalities shape the economic value and equitable use of agro-meteorological services.